Potential Role of Lymphovenous Bypass in Mitigating Alzheimer's Disease Dementia - Qingping Xie; Changsik John Pak; Jingeun Kwon; Sung-Chuan Chao; Joon Pio Hong (Archives of Plastic Surgery)
This case report explores the therapeutic potential of lymphovenous bypass (LVB) surgery performed at the neck in neurodegenerative diseases, specifically Alzheimer's disease (AD) dementia. The subject is a 58-year-old woman who was previously healthy but began experiencing unexplained memory decline and frequent disorientation in the past 7 years, leading to an AD diagnosis. Despite ongoing pharmaceutical therapy, her symptoms progressed to severe dementia accompanied by behavioral and psychological symptoms of dementia (BPSD). Her Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores were both 0/30, and 18F-AV-45 PET/CT revealed abnormal brain amyloid load. For salvage therapy, she underwent LVBs on her neck bilaterally. Postoperatively, she got better MMSE and MoCA scores with dramatic improvement in communication and activity. 18F-AV-45 PET/CT scans 4 months after surgery indicated a reduction in abnormal brain amyloid deposits. This case report highlights the potential effectiveness of LVB surgery in reducing brain amyloid load and attenuating cognitive impairment and BPSD. Further research with animal experiments and clinical trials is necessary to confirm these findings.